ON THE CHARACTERISTICS OF CIRCULATION IN THE UPWELLING REGION OF THE SOUTHERN VIETNAM - Vinh, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2007)
The main results of experimental investigation of the circulation characteristics in the upwelling region of the Southern Vietnam, based on the current data received in the cruises of the Vietnam-German Project “Upwelling”, are noted here. This project may be estimated as having the most detail current measurement and the biggest rate in this Vietnamese sea area. The current velocity can reach more than 100 cm/s. The main current direction is related to the monsoon directions: northeastern and southwestern. It may be formed two pictures of the horizontal circulation in the upwelling region of the Southern Vietnam in the eastwestern monsoon. The first is characterized by an eastern stream off the Vietnamese coast at the latitude of 120N. The second is characterized by forming of the two-layer circulation: in the surface layer there is current related to monsoon (it has mainly the northeastern direction) and in the subsurface layer - north - south direction current. The southern current can reach to the 100N latitude. The thickness of surface current is about 50 meters. And the subsurface current is located from the depth of 60 to about 130 meters. The longitude velocity component of these currents can reach more than 35 and 50 cm/s relatively. Here there noted some indirect methods for calculating the upwelling velocity and its application to this upwelling region. The results showed that the rate of upwelling velocities is 10-3 - 10-2 cm/s.